2019
DOI: 10.1002/1878-0261.12597
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CCCTC‐binding factor (CTCF) is linked to poor prognosis in prostate cancer

Abstract: The chromatin‐organizing factor CCCTC‐binding factor (CTCF) is involved in transcriptional regulation, DNA‐loop formation, and telomere maintenance. To evaluate the clinical impact of CTCF in prostate cancer, we analyzed CTCF expression by immunohistochemistry on a tissue microarray containing 17 747 prostate cancers. Normal prostate tissue showed negative to low CTCF expression, while in prostate cancers, CTCF expression was seen in 7726 of our 12 555 (61.5%) tumors and was considered low in 44.6% and high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The elimination of CTCF confirms the multifunctional state of the protein, which is an important factor in transcriptional regulation, unique ring formation, and maintenance of chromatin structure, and is involved in protein complexes, such as adhesion proteins in interchromatin and chromatin inner rings ( 32 - 35 ). Abnormal CTCF expression has been found to induce a number of diseases or disorders, including various types of cancer ( 31 , 36 ). In particular, the downregulation of CTCF is positively associated with the dysregulation of CpG methylation patterns around genes known to be involved in tumorigenesis such as tumor protein P53 (TRp53), DNA methyltransferase 1a (DNMT4a), Runt-related transcription factor 1 (RUNX1) and CTCF] ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The elimination of CTCF confirms the multifunctional state of the protein, which is an important factor in transcriptional regulation, unique ring formation, and maintenance of chromatin structure, and is involved in protein complexes, such as adhesion proteins in interchromatin and chromatin inner rings ( 32 - 35 ). Abnormal CTCF expression has been found to induce a number of diseases or disorders, including various types of cancer ( 31 , 36 ). In particular, the downregulation of CTCF is positively associated with the dysregulation of CpG methylation patterns around genes known to be involved in tumorigenesis such as tumor protein P53 (TRp53), DNA methyltransferase 1a (DNMT4a), Runt-related transcription factor 1 (RUNX1) and CTCF] ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70] . SNP rs820198 is annotated to an active CTCF (CCCTC-binding factor) binding site, and CTCF expression in linked to poor outcome in prostate cancer 71 . Although intergenic, SNP rs77112978 is near NEDD4L (MIM: 606384), whose expression is decreased in PC 72 .…”
Section: Discussionmentioning
confidence: 99%
“…RECQL5 (MIM: 603781), where SNP rs820198 is located, regulates DNA repair intermediate structures, and studies have observed elevated RECQL5 expression in other cancers such as breast (MIM: 114480) and bladder (MIM: 109800) 6870 . SNP rs820198 is annotated to an active CTCF (CCCTC-binding factor) binding site, and CTCF expression in linked to poor outcome in prostate cancer 71 . Although intergenic, SNP rs77112978 is near NEDD4L (MIM: 606384), whose expression is decreased in PC 72 .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of IRF1 (rabbit monoclonal antibody, Abcam, ab186384; dilution 1:450), TFAP2D [ 44 ], and CTCF [ 45 ] was performed similarly as described for PITX1. IRF-1 positive staining was usually seen in all tumor cells (100%).…”
Section: Methodsmentioning
confidence: 99%